Complicated crown fractures in maxillary central incisors restored by fragment reattachment technique: a three-dimensional finite element analysis - Dongqi Shi; Weijun Zhang; Yao Feng; Qiuyue Wang; Zhaolun Sun; Xiangling Liu; Lingbo Zhang (BMC Oral Health)
Abstract Objective This study utilized finite element analysis to investigate stress distribution in fragmented teeth treated with fragment reattachment technique(FRT). Study design Four complex crown fracture models were constructed using maxillary imaging data. Four restoration methods were devised: direct reattachment (GA), reattachment with a fiber post (GB), complete crown restoration (GC), and post-core crown restoration (GD). Results Comparison of stress distribution revealed that for identical fracture lines, the GB method had a significantly higher peak von Mises stress (VMS) in dentin than the GA method, while VMS in enamel was In the GC and GD methods, the peak VMS of the complete crown exceeded that of the enamel from the GA and GB methods. Additionally, the peak VMS of the resin core in GA and GB methods was less than that of the dentin. The peak VMS of adhesive layer 2 in the GD method was lower than in the GB method, with the average VMS of the fiber post in GD being lower than in GB. Conclusion FRT is a viable option for restoring complicated crown fractures. Closer proximity of the fracture line to the tooth neck increases debonding risk, and GD demonstrated superior stress performance under experimental conditions.